Pengaruh Kualitas Layanan terhadap Perilaku Pembelian melalui Image Konsumen (Studi Empiris pada Sanggar Senam Sagga di Kota Malang) - Sudarmiatin, Sudarmiatin (Universitas Brawijaya, Indonesia, 2009)
At global competition era, every marketer must be has innovations and creativities to interest their segmentation. The innovations and creativities are not only related to some goods and services, but also related with service quality which has given to customers. SAGGA Gymnasium is one of service business that’s giving the gymnastic services to comply the customer needs. The primary key to get their success is service quality. The general purpose in this research is to know some factors that impact consumer to choose SAGGA Gymnasium. That’s while, the specific purposes in this research are to know: (1) service quality condition (2) customer behavior condition (3) customer image condition and (4) impact of service quality on customer behavior which have mediated by consumer image. The samples in this research are 155 consumers of SAGGA Gymnasium at June up to July 2009. Sampling technique that used in this research is purposive sampling and instrument that used to gather the data is questioner. The results of this research are the service quality in SAGGA Gymnasium is good enough; consumer bought services in SAGGA Gymnasium to comply their needs on health; consumers’ image in SAGGA Gymnasium is good enough; and service quality impacted positive and significant on consumers’ behavior through consumers’ image.Keywords: Service quality, consumers’ behavior, consumers’ image.